Challenges and Priorities of Cooperation Between Higher Education and Business Community - Markoski, Goce; GJurovski, Marjan (“St. Kliment Ohridski” University - Bitola, 2021)
The aim of this paper is to contribute to a better perception of the need for cooperation of the Business community with the academy, i.e. Higher education. Considering the results of this type of cooperation at European level, compared to the situation in Macedonia, we can see a significantly lower fluctuation of activities in relation to this type of cooperation which is realized compared to EU countries. However, despite this situation, the Macedonian academic community still shows a very strong interest in the cooperation that should be achieved between Higher education and the Business community, which is reflected in the growing interest of companies to be part of this process. Thus, the positive attitude towards the cooperation of Higher education with the Business community, as well as the intention that exists to increase and improve this type of cooperation, can be strengthened by introducing tools and mechanisms supported by local and central government for greater involvement of Academia in Business community. The vision of the University "St. Kliment Ohridski”- Bitola, is to be exactly such a university, which with its work confirms the same. University St. Kliment Ohridski”- Bitola, has already imposed itself as a serious partner, offering cooperation with the Business community, which enables acceleration of development processes in both the University and Society. In that sense, the cooperation with the business community has wider dimensions and goals, due to which it will incorporate a range of issues that mean a more comprehensive approach to this issue, i.e. its connection with complementary and interdependent issues and problems related to it and synergistic effects from its implementation.
Keywords: Collaboration, University, Center, Students, Business